2012
DOI: 10.1016/s0924-9338(12)74668-0
|View full text |Cite
|
Sign up to set email alerts
|

P-501 - Use of donepezil for the treatment of depression in the absence of cognitive impairment

Abstract: Background: Donepezil is a reversible, centrally-acting acetylcholinesterase inhibitor used in the treatment of mild to moderate symptoms of dementia associated with Alzheimer's disease. In recent years, there has been emerging evidence of its use in other conditions, such as Lewy Body dementia and autism. However, there have been few reports of the use of Donepezil to treat depression in the absence of cognitive impairment. Methods: This is a case report of a 62-year old female with a long-standing history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results indicated the efficacy of donepezil in improving the symptoms of anxiety, depression, and cognition impairment (81). Moreover, in a case report by Lim et al, the antidepressant effect of donepezil at a dose of 5 mg as adjunctive therapy was noticed in a 62-year-old woman with a history of depression without any cognitive problems whose depression was resistant to routine depression treatments and even nextline drugs (82). However, as previously stated, some studies have shown inconsistent evidence regarding donepezil's efficacy in treating depression (80,83).…”
Section: Mood Disordersmentioning
confidence: 90%
“…The results indicated the efficacy of donepezil in improving the symptoms of anxiety, depression, and cognition impairment (81). Moreover, in a case report by Lim et al, the antidepressant effect of donepezil at a dose of 5 mg as adjunctive therapy was noticed in a 62-year-old woman with a history of depression without any cognitive problems whose depression was resistant to routine depression treatments and even nextline drugs (82). However, as previously stated, some studies have shown inconsistent evidence regarding donepezil's efficacy in treating depression (80,83).…”
Section: Mood Disordersmentioning
confidence: 90%